Pendidikan Islam di Era Bani Umayyah : Titik Awal Peradaban Ilmu - Syahrir, Thiesya Futri Amanda; Luthvia, Aulia; Nagara, Leksa Putri; Ifendi, Mahfud (Reflection : Islamic Education Journal, 2025)
This article aims to examine the development of Islamic education during the Umayyad Dynasty with a focus on two main aspects: how the Islamic education system was formed and the extent of the government's role in supporting it. By using a qualitative-descriptive approach based on historical studies, and including library research. Data collection techniques use various literature both from history books and from articles in national and international journals and conduct data analysis using content analysis. The results show that Islamic education during that period already had a functional structure through halaqah, mosques, and houses of scholars, although it had not been formally institutionalized. On the other hand, the Umayyad Dynasty government played an important role through Arabization policies, the construction of mosque infrastructure, and the creation of political stability that allowed science to develop. These findings underline that education during the Umayyad period grew from the synergy between community initiatives and structural support from the State.